2017
DOI: 10.3390/bioengineering4030075
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Olive Leaves Extracts in Biodegradable PLA Nanoparticles for Use in Cosmetic Formulation

Abstract: The aim of the current work was to encapsulate olive leaves extract in biodegradable poly(lactic acid) nanoparticles, characterize the nanoparticles and define the experimental parameters that affect the encapsulation procedure. Moreover, the loaded nanoparticles were incorporated in a cosmetic formulation and the stability of the formulation was studied for a three-month period of study. Poly(lactic acid) nanoparticles were prepared by the nanoprecipitation method. Characterization of the nanoparticles was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…In this work, a new protocol was developed, in order to link the extraction step directly to the precipitation one [21]. Indeed, the solvent phase was prepared by diluting a defined amount of the obtained extract (from 0.5 up to 1.5 mL), without any other preparative steps, up to a final volume of 15 mL, using the same extracting solvent.…”
Section: Production Of Zein Nanoparticles Loaded With H Sabdariffa Ementioning
confidence: 99%
See 1 more Smart Citation
“…In this work, a new protocol was developed, in order to link the extraction step directly to the precipitation one [21]. Indeed, the solvent phase was prepared by diluting a defined amount of the obtained extract (from 0.5 up to 1.5 mL), without any other preparative steps, up to a final volume of 15 mL, using the same extracting solvent.…”
Section: Production Of Zein Nanoparticles Loaded With H Sabdariffa Ementioning
confidence: 99%
“…Furthermore, the encapsulation protocols reported for extract stabilization are based on a first extraction step followed by a step of solvent removal and extract preparation for the encapsulation process. Then, other solvents are used to dissolve the polymer and the extract for the encapsulation step [21].…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is the use of chemically functionalised biodegradable polymeric carriers able to give enhanced properties over conventional carrier materials with the advantage of being nonreactive when in contact with the human body and metabolised and removed from the body via normal metabolic pathways [ 33 , 195 ]. The most commonly used shell materials in cosmetics are polysaccharides (gums, starches, celluloses, CDs and chitosan) [ 196 , 197 ]; proteins (gelatin, casein and soy proteins) [ 198 ]; lipids (waxes, paraffin and oils) [ 198 , 199 ] and synthetic polymers (acrylic polymers, polyvinyl alcohol and poly(vinylpyrrolidone)) [ 15 , 200 ]. Inorganic materials (silicates, clays and polyphosphates) can also be used [ 201 ].…”
Section: Applications Of Micro-/nanoencapsulated Fragrances and Flmentioning
confidence: 99%
“…PLA is a versatile polymer, which can be used for encapsulation purposes with a range of applications, e.g., within cosmetics. The study conducted by Kesente et al [4], demonstrated the potential of PLA nanoparticles for encapsulating olive leaves’ extract. The loaded nanoparticles were incorporated in cosmetic formulations.…”
mentioning
confidence: 99%
“…The encapsulated olive leaves’ extract showed a higher stability compared to pure extract and opens the possibility to better exploit the potential of plant and herb extracts rich in natural antioxidants. This can be used in topical formulations to enhance the skin’s endogenous protection system against oxidative damage [4]. Furthermore, encapsulation is an attractive approach for various products [5].…”
mentioning
confidence: 99%